The Association between the Socioeconomic Status and the Magnitude of HIV AIDS in Kinshasa - Ayikwa, Christian; ., Ben J van Rensburg (Journal of Economics and Behavioral Studies, 2014)
Researches devoted to the HIV/AIDS issue divide the scientific community between the supporters of an association socioeconomic status-HIV/AIDS and those estimating that there is no pattern between them. Studies conducted across the world’s most affected regions assert one another opinion on the basis of findings scientifically proven. In addition, some other studies argue that the link poverty-HIV/AIDS is vicious, meaning that poverty cause HIV/AIDS and vice versa. The present study conducted in Kinshasa, one of the African cities characterised by a certain level of poverty, aims at investing the potential correlation socioeconomic status and magnitude of HIV/AIDS in its specific context as well as contributes to the debate that took place in the scientific community between both mainstreams evoked previously. Although the study found no relationship between people socioeconomic status and either their sexual behaviour, HIV/AIDS knowledge (3 variables), accessibility to information or availability of condoms, as well as no statistically significant difference between socio economic groups in these mentioned variables, it estimates that it is all matter of space and time rather than pronouncing a judgement about who is right or wrong. Therefore no one is wrong, all are right.